KONTEN, TESTIMONI DAN KUALITAS PRODUK DIMEDIASI MINAT BELI: PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN PRODUK KORSET DI VIRALPRODUCTS.ID PADA PLATFORM TIKTOK - Angga Sambora; Ike Kusdyah Rachmawati; Theresia Pradiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Technology and social media have become an integral part of daily life. TikTok, one of the fastest-growing platforms, has evolved into an e-commerce platform known as TikTok Shop. With its socio-commerce concept, which combines social interaction and transactions, TikTok Shop offers an interactive, personalized, and community-based shopping experience, positioning itself as a disruptor in digital marketing across Southeast Asia, particularly in Indonesia. This study aims to analyze the influence of content, testimonials, and product quality on purchasing decisions, with purchase intent as a mediating variable, for Viralproducts.id corset products on the TikTok platform. The research was conducted in Malang City with a population of Viralproducts.id consumers. A sample of 100 respondents was selected using purposive sampling. Data analysis was conducted using path analysis with the assistance of SMART PLS 3. The results of the study indicate: (1) Content has a positive influence on purchase intent, (2) Testimonials have a positive influence on purchase intent, (3) Product quality does not influence purchase intent, (4) Purchase intention has a positive influence on purchase decision, (5) Content does not have a direct influence on purchase decision, (6) Testimonials do not have a direct influence on purchase decision, (7) Product quality does not have a direct influence on purchase decision, (8) Content has a positive influence on purchase decision through purchase intention, (9) Testimonials have a positive effect on purchasing decisions through purchase interest, and (10) Product quality has no effect on purchasing decisions through purchase interest. These findings emphasize the importance of content and testimonial strategies in increasing purchase interest, which ultimately influences purchasing decisions on socio-commerce platforms such as TikTok Shop.